The Effectiveness of Implementing a Project-Based Learning Model in Enhancing Arabic Speaking Skills for 11th-Grade Students at SMAN 1 Praya - Arifrabbani, Lalu Muhammad; Fadli, Adi; Maujud, Fathul (Jurnal Ilmiah Profesi Pendidikan, 2023)
This study is motivated by the low proficiency in Arabic speaking skills among 11th-grade students at SMAN 1 Praya. To address this issue, the research aims to evaluate the effectiveness of implementing a project-based learning model to enhance Arabic speaking skills. This study employs a mixed-methods approach, combining both quantitative and qualitative methods. Data collection techniques include observation, interviews, questionnaires, and speaking ability tests. Quantitative data were analyzed using descriptive and inferential statistics, while qualitative data were analyzed using thematic analysis techniques. The research findings indicate that the implementation of the project-based learning model significantly improves students' speaking skills. The conclusion drawn is that this model is effective in enhancing the Arabic speaking competency of 11th-grade students at SMAN 1 Praya. The implications of this study highlight the importance of adopting innovative teaching methods, such as project-based learning, to improve students' language abilities. Therefore, the results of this study can serve as a reference for teachers and educational institutions in selecting appropriate learning models to achieve optimal learning outcomes.